Quantifying Treatment - Outcome in Maxillo-Facial Injuries - Anil Agarwal; P S Chari; S Mitra (Indian Journal of Plastic Surgery, 1994)
Statements regarding outcome in Plastic Surgery are often subjective and lack reproducibility, mainly because of lack of quantification of aesthetic issues. A method is being presented using maxillo-facial injuries as a prototype, to resolve virtually any plastic surgical problem into 3 basic components – Function, Aesthetics and Psycho-social. Unfavourable results are graded according to a strictly defined protocol. Aesthetic evaluation is performed by the patient and relatives/friends in a manner designed to reduce subjectivity and physician-induced bias.